Prototype Sistem Monitoring Deteksi Dini Bencana Banjir Berbasis Internet Of Things (Iot) - Akhmed Alexander Zulkarnain Rhaisya; M Abil Athiyyah Fajar (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
This research describes the development of a prototype flood early warning system using Internet of Things (IoT) technology. This system utilizes an HC-SR04 ultrasonic sensor integrated with an ESP32 microcontroller to detect and monitor air level in real-time. The prototype is equipped with LED indicators, a buzzer, and an LCD display to provide progressive warnings based on air level. Green, yellow, and red LEDs indicate safe (below 50 cm), warning (50-100 cm), and danger (above 100 cm), respectively, with a buzzer sounding when a dangerous situation occurs. The system is also integrated with the Blynk IoT platform, enabling remote monitoring via smartphone. This innovative approach demonstrates the potential of IoT technology in disaster preparedness and provides an alternative solution for air level monitoring and flood early warning systems. The system's flexibility allows parameter adjustments according to different field conditions, making it easily adaptable to varying scenarios. This prototype aims to improve community safety and preparedness for flood risks and opens opportunities for further development and large-scale implementation in more flood-prone areas.